Effects of enzyme dosage on glucose production from pretreated sago hampas - Muhammad Siddiq, Bin Mohamed Salleh. (Universiti Malaysia Sarawak (UNIMAS), 2014)
Nowadays, the depletion of carbon sources likes glucose could be aided by utilizing free waste from sago hampas that contain more than 50% starch. In order to increase the utilization of sago hampas, this study was conducted to determine the effects of spirizyme dosage on glucose production from steaming pretreated sago hampas. Three different enzyme dosage were selected which are 0.25 µl/g, 0.5 µl/g, and 1.0 gl/g. The sequential step enzymatic hydrolysis and optimum enzyme loading can be the alternate way to saving the time and the cost of operation. Steaming process which considered as pretreatment stage for further hydrolysis was applied initially before enzymatic hydrolysis. Based on the analysis, the 0.5 µl/g of Spirizyme used is selected as the highest productivity and glucose generated 51.10% (w/w) can be attained at 2 hours only. Interestingly, by using only 0.25 gl/g of Spirizyme the conversion was fairly efficient and as high as 50.19% (w/w). This conversion rate could be considered economically feasible regarding the consumption of enzyme dosage and finally the cost of product. The left fibre treated with celluclast and (3-glucosidase, show the higher production of cellobiose than glucose. The enzyme productivity is less as the glucose released less than 0.2 g/L/h and uneconomical for large scale processing.